Does kidney transplantation with a standard or expanded criteria donor improve patient survival? Results from a Belgian cohort. Issue 5 (26th February 2021) - Hellemans, Rachel; Kramer, Anneke; De Meester, Johan; Collart, Frederic; Kuypers, Dirk; Jadoul, Michel; Van Laecke, Steven; Le Moine, Alain; Krzesinski, Jean-Marie; Wissing, Karl Martin; Luyckx, Kim; van Meel, Marieke; et al.
Abstract: Background: Changes in recipient and donor factors have reopened the question of survival benefits of kidney transplantation versus dialysis. Methods: We analysed survival among 3808 adult Belgian patients waitlisted for a first deceased donor kidney transplant from 2000 to 2012. The primary outcome was mortality during the median waiting time plus 3 years of follow-up after transplantation or with continued dialysis. Outcomes were analysed separately for standard criteria donor (SCD) and expanded criteria donor (ECD) kidney transplants. We adjusted survival analyses for recipient age (20–44, 45–64 and ≥65 years), sex and diabetes as the primary renal disease. Results: Among patients ≥65 years of age, only SCD transplantation provided a significant survival benefit compared with dialysis, with a mortality of 16.3% [95% confidence interval (CI) 13.2–19.9] with SCD transplantation, 20.5% (95% CI 16.1–24.6) with ECD transplantation and 24.6% (95% CI 19.4–29.5) with continued dialysis. Relative mortality risk was increased in the first months after transplantation compared with dialysis, with equivalent risk levels reached earlier with SCD than ECD transplantation in all age groups. Conclusions: The results of this study suggest that older patients might gain a survival benefit with SCD transplantation versus dialysis, but any survival benefit with ECD transplantation versus dialysis may be small. Graphical Abstract: